Feasibility of a Virtual Educational Programme for Behaviour Change in Cardiac Patients from a Low-Resource Setting - Santos R.Z.D.* (2023)
© 2023 by the authors.Patient education is an integral part of recovery from a critical cardiac life event and a core component of cardiac rehabilitation (CR) programmes. This study addressed the feasibility of a virtual educational programme for behaviour change in CR patients from a low-resource setting in Brazil. Cardiac patients from a CR programme closed due to the pandemic received a 12-week virtual educational intervention (WhatsApp messages and bi-weekly calls from healthcare providers). Acceptability, demand, implementation, practicality, and limited efficacy were tested. Overall, 34 patients and 8 healthcare providers agreed to participate. The intervention was considered practical and acceptable by the participants, who reported a satisfaction median of 9.0 (7.4–10.0)/10 (patients) and 9.8 (9.6–10.0)/10 (providers). The main difficulties in carrying out the intervention activities were related to technology, motivation to self-learning, and a lack of in-person orientation. All the patients reported that the information included in the intervention was aligned with their information needs. The intervention was associated with changes in exercise self-efficacy, sleep quality, depressive symptoms, and performance of high-intensity physical activity. In conclusion, the intervention was considered feasible to educate cardiac patients from a low-resource setting. It should be replicated and expanded to support patients that face barriers to onsite CR participation. Challenges related to technology and self-learning should be addressed.